Biological Information 2013
DOI: 10.1142/9789814508728_0020
|View full text |Cite
|
Sign up to set email alerts
|

Getting There First: An Evolutionary Rate Advantage for Adaptive Loss-of-Function Mutations

Abstract: Over the course of evolution organisms have adapted to their environments by mutating to gain new functions or to lose pre-existing ones. Because adaptation can occur by either of these modes, it is of basic interest to assess under what, if any, evolutionary circumstances one of them may predominate. Since mutation occurs at the molecular level, one must look there to discern if an adaptation involves gain-or loss-of-function. Here I present a simple, deterministic model for the occurrence and spread of adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…However, this did not actually involve evolution of a new function -the E. coli already had all the machinery needed for metabolizing citrate, but the citrate could not normally pass through the bacteria's external membrane. In light of the work of Behe [61], in such a case the most likely explanation for this mutant strain would be a loss-of-function mutation that would result in a leaky membrane. Certainly no exhaustive research was done to prove that the mutation in question had zero deleterious effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, this did not actually involve evolution of a new function -the E. coli already had all the machinery needed for metabolizing citrate, but the citrate could not normally pass through the bacteria's external membrane. In light of the work of Behe [61], in such a case the most likely explanation for this mutant strain would be a loss-of-function mutation that would result in a leaky membrane. Certainly no exhaustive research was done to prove that the mutation in question had zero deleterious effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews [8,10,99] have reported that the majority of studied adaptations involve the loss of traits and the reduction of genetic information. Whether a mutation is beneficial may depend critically upon the environment in which it arises (e.g., whether nutrients are available or antibiotics are present), meaning that the effect of a mutation on genetic information cannot be inferred from relative growth rates alone.…”
Section: Reducti Ve Evoluti Onmentioning
confidence: 99%
“…A survey of lab experiments showed that the adaptations found in such scenarios fit the same picture [26]. Further discussion of adaptation by loss in biological scenarios can be found within these proceedings [27].…”
Section: Discussionmentioning
confidence: 81%